A mulher negra e a discriminação racial: os desafios e enfrentamentos no mercado de trabalho - Cruz, Diana Costa da (Universidade Federal do Tocantins, 2024)
This study aims to analyze the main factors that perpetuate the inequalities faced by black women in the job market. The research consisted of a bibliographic review, as it sought to analyze the research object through access to data and information present in articles, books, and other literature. The review was carried out by accessing the databases of the Virtual Health Library–Psychology Brazil (BVSPsi) and Scientific Electronic Library Online (SciELO), in addition to consulting important publications in the literature for the debate on race and gender. The inclusion criteria adopted were: works in Portuguese and Spanish published between 1985 and 2022; analyses on gender, race, and racism, feminism and black feminism, and the job market, prepared in the areas of Psychology and human sciences. The exclusion criteria used were: studies carried out in a foreign language; articles in which the object of analysis does not deal with racism and the issues listed above. The 1980s were important because black feminism gained strength in Brazil from that decade onwards. It was possible to identify the difficulty of black women in advancing professionally, both due to the difficulty of accessing quality education or when this knowledge is overlooked due to the idea that they do not have the capacity to perform this function. Therefore, it was identified that racism is a fundamental factor in perpetuating this cycle of subordinate jobs, especially in relation to black women who end up suffering from double discrimination due to race and gender.